FORECASTING FREEPORT-MCMORAN STOCK PRICE USING LOCALLY STATIONARY WAVELET - Vega Zayu Farima; Indah Manfaati Nur (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
PT Freeport Indonesia is the manager of the Grasberg Mine in Papua, Indonesia, which is one of the largest gold mines in the world. This mine also contains copper and silver for the world market. Freeport McMoRan'sshareholder has recently trending topic because its shares have been purchased by the Indonesian government.This stock price value has a very high volatility and tend not stationary. Wavelet transformation is capable ofrepresenting functions that are not smooth or have high volatility. Locally Stationary Wavelet (LSW) is aforecasting model by minimizing error values and capturing most of the time series data information. In thisresearch we can get stock price of Freeport-McMoran stationary after differencing. Stock price forecasting usingLSW yields a small MAPE value of 1.94%. This indicates that the LSW model is good for forecasting usingstock price data. Keywords: Freeport McMoRan, Stasionary, LSW, MAPE